Mode investigation of CO2 sorption enhancement for titanium dioxide-decorated CaO-based pellets. (15th November 2019) - Sun, Jian; Guo, Yafei; Yang, Yuandong; Li, Weiling; Zhou, Yue; Zhang, Jubing; Liu, Wenqiang; Zhao, Chuanwen
Graphical abstract: Highlights: The TiO2 -decorated CaO-based pellets were prepared via extrusion-spheronization. The modes of dry-mixing, wet-mixing and hydration-mixing were compared. Hydration-mixing is a promising mode to prepare TiO2 -decorated CaO-based pellets. Strong binding force of the hydrate contributes to high anti-attrition ability. Abstract: The rapid loss-in-capacity and severe attrition are easily encountered for CaO-based sorbent during multiple CO2 capture cycles. It is necessary to prepare the CaO-based CO2 capture sorbent with high capability for CO2 uptake and attrition resisting. In this work, the TiO2 -decorated CaO-based sorbent pellets were prepared via extrusion-spheronization, and three different modification modes (i.e., dry-mixing, wet-mixing and hydration-mixing) were applied. This paper lay emphasis on investigating the modification mode on affecting the cyclic CO2 uptake and anti-attrition ability of TiO2 -decorated CaO-based sorbent pellets. It is found that hydration-mixing is superior to dry-mixing and wet-mixing on modifying the CO2 capture performance of TiO2 -decorated CaO-based sorbent pellets. The TiO2 -decorated CaO-based sorbent pellets containing 20 wt% of TiO2 prepared via hydration-mixing exhibit the highest 25th carbonation conversion of 53.44% and a desirable anti-attrition ability (a weight loss of 0.62% after 3000 rotations). The alleviated sorbent sintering as a result of the homogeneously distributed CaTiO3 phase is responsible for the improved CO2 capture performance. Additionally, the strong binding force of the initially formed hydrate contributes to enhancing the anti-attrition ability of the TiO2 -decorated CaO-based sorbent pellets prepared via hydration-mixing.